1988
DOI: 10.1038/bjc.1988.60
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monoclonal antibody Ki-67 reactivity with grade and DNA flow cytometry of breast carcinomas

Abstract: Summary The reactivity of 95 breast carcinomas with the antibody Ki-67, which recognises a nuclear antigen in proliferating cells, has been assessed and compared to their histological grade and, for 47 tumours, DNA index and S-phase content. The effects of freezing and section handling on the stability of the nuclear antigen have been assessed.Evidence of nuclear staining was seen in 56% of carcinomas, with a range of positive cells from <1% to 60%. Cytoplasmic rather than nuclear staining was observed in 26% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 12 publications
6
48
1
Order By: Relevance
“…The strong association between the extent of nuclear area staining with MIBI antibody and histological grade is similar to that we have reported previously with Ki-67 (Bouzubar et al, 1989) and which has been noted by others (Walker and Camplejohn, 1988;Betta et al, 1989;Wrba et al, 1989;Dawson et al, 1990). This correlation with histological grade is strong; however, in multivariate analysis MIBI labellng is of indepenent prognostic sign .…”
Section: Tissuesupporting
confidence: 78%
See 2 more Smart Citations
“…The strong association between the extent of nuclear area staining with MIBI antibody and histological grade is similar to that we have reported previously with Ki-67 (Bouzubar et al, 1989) and which has been noted by others (Walker and Camplejohn, 1988;Betta et al, 1989;Wrba et al, 1989;Dawson et al, 1990). This correlation with histological grade is strong; however, in multivariate analysis MIBI labellng is of indepenent prognostic sign .…”
Section: Tissuesupporting
confidence: 78%
“…In breast carcinomas, although some have found no association between Ki-67 immunoreactivity and other prognostic variables (Stumpp et al, 1992), many authors have reported an association with histological grade (Walker and Camplejohn, 1988;Betta et al, 1989;Bouzubar et al, 1989;Wrba et al, 1989;Dawson et al, 1990). Associations with lymph node status (Wrba et al, 1989), patient's age (Sahin et al, 1991), tumour size (Wrba et al, 1989;Veronese and Gambacorta, 1991), oestrogen and progesterone receptor status (Wrba et al, 1989;Campani et al, 1991;Di-Stefano et al, 1991;Veronese and Gambacorta, 1991), ploidy (Dawson et al, 1990;Isola et al, 1990;Lee et al, 1992), p53 (Barbareschi et al, 1992) (1991) showed that the response to endocrine therapy of a breast carcinoma was related to the degree of Ki-67 immunoreactivity, and an association between Ki-67 staining and both disease-free interval and survival has been reported (Veronese et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies suggest that the interferons should be useful in the treatment of breast cancer, modulating both tumour The alterations induced by IFN pretreatment on the expression of the proliferation associated antigen Ki 67, which has previously been shown to correlate with mitotic index, 'S' phase fraction and prognosis in breast cancer (Barnard et al, 1987;Walker & Camplejohn, 1988), were those which were predicted from the in vitro anti-proliferative effects of IFN. Both the patients who had initial high Ki 67 expression, showed significant reduction after IFN and both responded to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found an association between Ki-67 expression and other prognostic variables (Walker and Camplejohn, 1988;Wintzer et al, 1991). Until recently, the most significant limitation to the use of monoclonal Ki-67 was the need for frozen material, as the antigen is very sensitive to fixation and prolonged storage (Neubauer and Hunn, 1987).…”
mentioning
confidence: 99%